Dynamics of the difference equation xn = a - Xn-kp/xn-mq - Li H.E. (Utilitas Mathematica, 2013)
This paper studies the periodic character and stability of positive solutions to the nonlinear difference equation xn = A - xn-kp/xn-mq, n ε ℕ0, where A > 1, p ≥ q > 0 and k, m ε ℕ, k ≠ m.